1975
DOI: 10.1007/bf00567127
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant effect and plasma kinetics of fluorophenindione after a single dose in man

Abstract: After administration of a single loading dose (80 mg p.o.) of fluorophenindione, the prothrombin level decreased to 37% in 24 h, and the effect lasted for 48 h. Accordingly, fluorophenindione can be classified as an anticoagulant with an ""intermediate'' effect. Its elimination half-life was 31 h, which is longer than that of phenindione, because of the greater stability of the fluorinated derivate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1975
1975
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…An intermediate half-life has been described for fluindione, similar to the half-life of the more potent enantiomer of warfarin [ 18 ]. One study described a fluindione half-life of 31h [ 71 ], while another found a median half-life of 69h [ 70 ]. Fluindione is less often displaced by other drugs in their receptors and it has higher affinity to albumin than warfarin [ 70 ].…”
Section: Vitamin K Antagonist (Vka)mentioning
confidence: 99%
“…An intermediate half-life has been described for fluindione, similar to the half-life of the more potent enantiomer of warfarin [ 18 ]. One study described a fluindione half-life of 31h [ 71 ], while another found a median half-life of 69h [ 70 ]. Fluindione is less often displaced by other drugs in their receptors and it has higher affinity to albumin than warfarin [ 70 ].…”
Section: Vitamin K Antagonist (Vka)mentioning
confidence: 99%
“…Most 2-aryl-l,3-indandiones have been found to be rapidly and almost completely absorbed from the gastrointestinal tract (5,15,16).…”
Section: Introductionmentioning
confidence: 99%
“…According to this model the following equations apply:after i.v. The data on the absorption and elimination, cited in the Introduction, were determined at about 280 (IS) or 338(5,16) nm. It hasrecently been demonstrated that the oxidation products of PID absorb at the same wavelengths(18).…”
mentioning
confidence: 99%